Question
upstudy study bank question image url

Given the system of equations, what is the solution? \( \begin{array}{l}3 x-2 y+10=0 \\ 5 y=4 x+8 \\ \{(-34 / 7,-16 / 7)\} \\ \{(-34 / 7,16 / 7)\} \\ \{(34 / 7,-16 / 7)\}\end{array} \)

Ask by Moran Ayala. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = -\frac{34}{7} \) and \( y = -\frac{16}{7} \).

Solution

Solve the system of equations \( 3x-2y+10=0;5y=4x+8 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x-2y+10=0\\5y=4x+8\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{2y-10}{3}\\5y=4x+8\end{array}\right.\) - step2: Substitute the value of \(x:\) \(5y=4\times \frac{2y-10}{3}+8\) - step3: Simplify: \(5y=\frac{4\left(2y-10\right)}{3}+8\) - step4: Multiply both sides of the equation by LCD: \(5y\times 3=\left(\frac{4\left(2y-10\right)}{3}+8\right)\times 3\) - step5: Simplify the equation: \(15y=8y-16\) - step6: Move the variable to the left side: \(15y-8y=-16\) - step7: Subtract the terms: \(7y=-16\) - step8: Divide both sides: \(\frac{7y}{7}=\frac{-16}{7}\) - step9: Divide the numbers: \(y=-\frac{16}{7}\) - step10: Substitute the value of \(y:\) \(x=\frac{2\left(-\frac{16}{7}\right)-10}{3}\) - step11: Calculate: \(x=-\frac{34}{7}\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{34}{7}\\y=-\frac{16}{7}\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{34}{7}\\y=-\frac{16}{7}\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{34}{7},-\frac{16}{7}\right)\) The solution to the system of equations is \( (x,y) = (-\frac{34}{7},-\frac{16}{7}) \) or \( (x,y) = (-4.857142, -2.285714) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations, let's first rearrange both equations to make them easier to work with. 1. The first equation can be rearranged as: \( 3x - 2y = -10 \) or \( 3x = 2y - 10 \). 2. The second equation is: \( 5y = 4x + 8 \) or \( 5y - 4x = 8 \). Now we can solve for one variable in terms of the other. Let's solve the first equation for \(y\): \[ 2y = 3x + 10 \implies y = \frac{3}{2} x + 5. \] Next, substitute this expression for \(y\) into the second equation: \[ 5\left(\frac{3}{2} x + 5\right) - 4x = 8. \] Expanding this gives: \[ \frac{15}{2} x + 25 - 4x = 8. \] To eliminate the fraction, we can multiply the entire equation by 2: \[ 15x + 50 - 8x = 16 \implies 7x + 50 = 16 \implies 7x = -34 \implies x = -\frac{34}{7}. \] Now, plug \(x\) back into the equation for \(y\): \[ y = \frac{3}{2} \left(-\frac{34}{7}\right) + 5 = -\frac{102}{14} + 5 = -\frac{102}{14} + \frac{70}{14} = -\frac{32}{14} = -\frac{16}{7}. \] So the solution to the system of equations is: \[ \boxed{\left(-\frac{34}{7}, -\frac{16}{7}\right)}. \] It appears that option \( \{(-34 / 7,-16 / 7)\} \) is indeed the correct choice!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy